Molecular and Immunologic Characterization of Gynogenetic Channel Catfish (Ictalurus punctatus). - Hogan, R; Waldbieser, G; Goudie, C; Antao, A; Godwin, U; Wilson, MR; Miller, N; Clem, L; McConnell, T; Wolters, W; Chinchar, V (1999)
: Second-generation gynogenetic channel catfish were characterized by molecular and immunologic assays to determine if they were isogenic at major histocompatibility complex loci. Southern blot analyses, using channel catfish MHC class II B and class I A gene probes, revealed identical banding patterns among second-generation gynogenetic fish. In contrast, banding patterns from outbred fish differed not only from gynogenetic animals, but also among themselves. Nucleotide sequence analysis of the MHC class II beta(1) domain, which encompasses the peptide binding region, from four randomly selected gynogenetic fish showed a single DNA sequence. In contrast, analysis of the same region from three outbred fish showed sequences that differed not only among themselves, but also from those of gynogenetic animals. In cytotoxic assays, peripheral blood leukocytes from outbred fish lysed both gynogenetic and allogeneic targets, whereas those from gynogenetic fish lysed only allogeneic targets. Taken together, these results suggest that this group of second-generation gynogenetic channel catfish is isogenic at MHC loci and may provide an excellent system with which to study cell-mediated immunity in teleosts.